Electrochemical deposition of neodymium in LiF-CaF2 from Nd2O3 assisted by AlF3. (20th January 2018) - Chen, Zi; She, Changfeng; Zheng, Haiyang; Huang, Wei; Zhu, Tiejian; Jiang, Feng; Gong, Yu; Li, Qingnuan
Abstract: This paper investigated the co-reduction process of Al-Nd alloys and the electrochemical extraction of neodymium from neodymium oxide in LiF-CaF2 melt. Nd(III) at a tungsten electrode was reduced to Nd(0) through a one-step process involving the exchange of three electrons: Nd(III) + 3e − = Nd(0). The fluorination of Nd2 O3 by AlF3 produced Nd(III) ions in the LiF-CaF2 molten salts. The co-reduction behavior of Nd(III) and Al(III) ions was studied on a W electrode in the LiF-CaF2 -AlF3 -Nd2 O3 system. Four types of intermetallic Al-Nd compound were detected through cyclic voltammetry and open circuit chronopotentiometry. The Nd3 Al and NdAl phases were identified through X-ray diffraction, and the NdAl3 and Nd3 Al11 phases were characterized by a scanning electron microscope equipped with an energy dispersive spectrometer.